Handling Tone in Two-Level Morphology - Lotta Harjula (Nordic Journal of African Studies, 2004)
The problem of handling tone in morphological parsing has not yet been widely addressed. The morphological parsers are typically developed for languages without contrastive tonal systems, and the application of such parsers need to be adapted to handle tonal phenomena. The major problem, especially with African tone languages, is the fact that the tonal features often function on a level separate from the segmental level and would thus require a level of description of their own. The purpose of this paper, however, is to show that the Two-Level approach is sufficient to handle at least the pitch-accent type system of tone in Ha.